Transient Simulation of a Dual-evaporator air Conditioning System for Developing an Improved Humidity Control Strategy. (August 2015) - Yan, Huaxia; Deng, Shiming
Abstract: This paper presents a mathematic model for predicting the dynamic performance and developing an improved humidity control strategy of a Dual-evaporator air conditioning (DEAC) system. The model is built based on component sub-models. Using the DEAC model developed, simulation studies were carried out under multi-evaporator operation and single-evaporator operation, respectively. Dynamic effects of the multi-evaporator operation suggested that the model developed could predicate the transient performance of the DEAC system over a wide range of operating conditions. Therefore, it can be used as a useful tool in investigating the control performance of a DEAC system. A previously developed High-Low control strategy for improved indoor humidity control was incorporated into the developed DEAC model. At the first stage, only the single-evaporator operation under the H-L control was simulated. The simulation study has produced similar results to the previously experimental results on H-L control and thus paved the way to studying applying the H-L control to a DEAC system for better indoor humidity control.